THE EFFECTIVENESS OF SCIENTIFIC APPROACH-BASED SCIENCE LEARNING MATERIALS TO EDUCATE STUDENTS SCIENCE LITERACY - Arfiati Ulfa Utami; Selly Candra Citra Murti (JPPS (Jurnal Penelitian Pendidikan Sains), 2018)
The purpose of this research is to test the effectiveness of scientific approach-based science learning materials. Data collection techniques include: observation, test, and questionnaires. Research instruments include; sheets of learning implementation using scientific approach-based science learning materials, test, and questionnaires. Technique of data analysis used was classical mastery analysis on test result of learning (cognitive). In this research the effectiveness of scientific approach-based science learning materials can be measured through: (1) learning implementation, (2) learning outcomes, (3) activities, (4) students responses. Percentage of learning achievement reached 83,8% with well executed category, the percentage of students learning outcomes on cognitive aspect in terms of classical mastery in replication I and II reached 82.8% and 85.7% with complete category, the percentage of students activities on replication I and II reached 84.11 and 83.23 with active category and the percentage of students' respons reached 82% with positive response category. Based on the data exposure, the implementation of scientific approach-based science learning materials was effective to educate students science literacy